(untitled) (Bioagro, 2024)
Given the importance of research related to the use of Bacillus endophytes as biological control agents of Moniliophthora roreri, the objective of this study was to evaluate the effect of four strains of this bacterial genus in the protection of Theobroma cacao L. against the causal agent of moniliasis in a production area of the province of Esmeraldas, Ecuador. The experiment was conducted in an established plantation with the 14-year-old cocoa genotype EET-103 Nacional type, with a 3 x 3 m frame, on an Andisol soil, under a randomized complete block design, with six treatments and five replications. Three applications were made at a monthly frequency. Incidence and external severity were evaluated on the pod during the 90 days of development at a biweekly frequency. When the pods reached harvest maturity, they were opened longitudinally and the percentage of internal severity was determined. It was found that all strains showed biocontrol effect on M. roreri under field conditions, with Bacillus sp. 33 and B. amyloliquefaciens 24, isolated from the fruit mesocarp, standing out with average incidence values between 4.4 and 7.6 %, external severity between 3.6 and 6.2 % and internal severity between 22-30 %, respectively. The application of Bacillus endophytes strains constitutes a biological alternative to reduce the effects of moniliasis in cocoa agroecosystems.